Dietary diversity predicts the adequacy of micronutrient intake in pregnant adolescent girls and women in Bangladesh, but use of the 5-group cutoff poorly identifies individuals with inadequate intake - Nguyen, Phuong Hong; Huybregts, Lieven; Sanghvi, Tina; Tran, Lan Mai; Frongillo, Edward A.; Menon, Purnima; Ruel, Marie T. (Oxford University Press, 2018)
Background: The Minimum Dietary Diversity for Women (MDD-W) indicator based on a 10-food group women dietary diversity score (WDDS-10) has been validated to assess dietary quality in nonpregnant women. Little is known about its applicability in pregnant women, and specifically pregnant adolescent girls with higher nutrient requirements.